Model Gelombang di sekitar Hexagonal Artificial Reef sebagai Submerged Breakwater Menggunakan DUALSPHYSICS - Armono, Haryo Dwito; Manurung, Adelbert; Sujantoko, Sujantoko (Universitas Trunojoyo Madura, 2022)
The functions and uses of artificial reef have evolved from a method of coral reefs restoration to a coastal protection system. Artificial reef can reduce the hydraulic load on the coast to the level required to maintain shoreline balance. Various materials and shape of artificial reefs have been introduced. This paper discussed the wave transmission over hexagonal-shaped artificial reef with 6 holes on each side. The study was conducted using the Smoothed Particle Hydrodynamic (SPH) method integrated in DualSPHysics software to see the effect of gaps between structures with a predetermined configuration to the value of the transmission coefficient (Kt). It was found that the configuration with no gap was able to absorb waves better than the configuration with a gap of 0.15 m and 0.112 m based on the Kt value obtained. In terms of hydrodynamics, it was found that: (1) The increment of the wave steepness, the smaller the Kt value obtained, (2) The larger the wave height, the smaller the Kt value at 0.1 m freeboard depth, while on the freeboard with a depth of 0.2 m and 0.3 m, it was found that the greater the wave height, the greater the Kt value, (3) the increment of the wave period, the Kt were higher, and also (4) the higher the freeboard, the higher the Kt.